2016
DOI: 10.3389/fmicb.2015.01550
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Aminoglycoside Subsistence Phenotype of Bacteria Residing in the Gut of Humans and Zoo Animals

Abstract: Recent studies indicate that next to antibiotic resistance, bacteria are able to subsist on antibiotics as a carbon source. Here we evaluated the potential of gut bacteria from healthy human volunteers and zoo animals to subsist on antibiotics. Nine gut isolates of Escherichia coli and Cellulosimicrobium sp. displayed increases in colony forming units (CFU) during incubations in minimal medium with only antibiotics added, i.e., the antibiotic subsistence phenotype. Furthermore, laboratory strains of E. coli an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
(40 reference statements)
0
12
0
Order By: Relevance
“…Finally, antibiotic-catabolizing enzymes have the potential to play an important industrial role in the production of next-generation antibiotics in the same way that the discovery of penicillin amidase spurred the development of semi-synthetic β-lactams through remodeling of natural penicillins. Characterization of hydrolytic enzymes responsible for the catabolism of other antibiotics, such as hypothetical glycosidases acting on aminoglycosides 16 , could catalyze an explosion of diverse semi-synthetic derivatives in other antibiotic classes. Antibiotic degradation may therefore paradoxically contribute to the development of the next generation of novel antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, antibiotic-catabolizing enzymes have the potential to play an important industrial role in the production of next-generation antibiotics in the same way that the discovery of penicillin amidase spurred the development of semi-synthetic β-lactams through remodeling of natural penicillins. Characterization of hydrolytic enzymes responsible for the catabolism of other antibiotics, such as hypothetical glycosidases acting on aminoglycosides 16 , could catalyze an explosion of diverse semi-synthetic derivatives in other antibiotic classes. Antibiotic degradation may therefore paradoxically contribute to the development of the next generation of novel antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…However, controversy still remains over the characterization of resistant, but not metabolizing, versus subsistent growth phenotypes. To date, no specific genes or pathways have been identified that enable bacteria to use antibiotics as a sole carbon source 16 , 20 .…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of aminoglycosides in the sewage samples was performed as in Bello 53 , with adaptations as summarized in the following. For sample pretreatment, two 10-mL portions of each sample of sewage were weighed into separate 50-mL tubes, after which internal standards were added.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, very recently, RNA-hydrolysis activity of bacterial class B metallo-β-lactamase IMP-1 has been reported experimentally [ 28 ]. The use of antibiotics as a source of nutrients for archaebacteria to degrade the molecules of β-lactam and use them as a source of carbon, as described in the bacteria, is a plausible hypothesis [ 20 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%